2018
DOI: 10.1177/0363546518769295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Platelet-Rich Plasma Treatment on Postoperative Donor Site Knee Pain in Patellar Tendon Autograft Anterior Cruciate Ligament Reconstruction: A Double-Blind Randomized Controlled Trial

Abstract: Whether randomized to receive PRP in their patellar defect or not, patients continued to have similar levels of kneeling pain and patellar defect sizes after autograft BPTB ACL reconstruction. Registration: NCT01765712 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 43 publications
(59 reference statements)
1
88
0
1
Order By: Relevance
“…Three studies were at high risk of bias for two domains [36,39,43], eight studies were at high risk of bias for one domain [30,[32][33][34][35]40,42,44], and one study was at high risk of bias for two domains with a risk of reporting bias for one domain [38]. High risk of performance bias was identified in one study [38], a moderate risk of performance bias was identified in twelve studies [30,[32][33][34][35][36]39,40,[42][43][44]46], and a low risk of performance bias was identified in three studies [29,31,41].…”
Section: Anterior Cruciate Ligament Reconstruction (Acl)mentioning
confidence: 98%
See 2 more Smart Citations
“…Three studies were at high risk of bias for two domains [36,39,43], eight studies were at high risk of bias for one domain [30,[32][33][34][35]40,42,44], and one study was at high risk of bias for two domains with a risk of reporting bias for one domain [38]. High risk of performance bias was identified in one study [38], a moderate risk of performance bias was identified in twelve studies [30,[32][33][34][35][36]39,40,[42][43][44]46], and a low risk of performance bias was identified in three studies [29,31,41].…”
Section: Anterior Cruciate Ligament Reconstruction (Acl)mentioning
confidence: 98%
“…Sixteen RCTs, including 740 patients, evaluated the use of PRP as an adjunct to ACL reconstruction with patellar ligament (Bone-Patella Tendon-Bone-BPTB) autograft [29][30][31][32][33][34][35] or hamstrings graft [33,[36][37][38][39][40][41][42][43][44] (Table 6).…”
Section: Anterior Cruciate Ligament Reconstruction (Acl)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial, Cervellin et al found that patients who had PRP applied to the patellar tendon donor site following ACL reconstruction experienced a significant decrease in knee pain and improved function at 1 year [38•]. This finding, however, has not been consistent in the literature [40]. Walters et al recently performed a randomized control trial examining the use of PRP in reducing kneeling pain at the donor site of ACL reconstruction [40].…”
Section: Patellar Tendinopathymentioning
confidence: 99%
“…Walters et al recently performed a randomized control trial examining the use of PRP in reducing kneeling pain at the donor site of ACL reconstruction [40]. Their study found no difference in kneeling pain at interval follow-up between patients who received PRP versus placebo [40].…”
Section: Patellar Tendinopathymentioning
confidence: 99%